THE EFFECTIVENESS OF LEADERSHIP STYLES IN EFFORTS TO MAINTAIN TRADITIONAL ISLAMIC BOARDING SCHOOL CULTURE AS LOCAL WISDOM OF ACEH - Zahraini, Zahraini; Amalina, Zahria; Akmaluddin, Akmaluddin; Sari, Siti Mayang (Universitas Labuhanbatu, 2025)
Purpose – This study aimed to determine the effectiveness of leadership style in Islamic boarding schools in preserving the traditional Islamic boarding school culture as local wisdom of Aceh.Methodology – This study uses a quantitative approach with a descriptive-correlational design through a structured questionnaire on the leaders, teachers, and staff of the Insafuddin Integrated Islamic Boarding School, Banda Aceh. The data were analyzed using descriptive and inferential statistics, including normality tests, multicollinearity, heteroscedasticity, Pearson correlation, and simple linear regression to measure the influence of leadership style on the maintenance of Islamic boarding school culture.Findings – This study shows that leadership style positively affects efforts to maintain the traditional Islamic boarding school culture, as the local wisdom of Aceh. The results of simple linear regression analysis show a regression coefficient value of 0.533 and a determination coefficient (R²) of 0.211, which means that leadership style explains 21.1% of the variation in efforts to preserve Islamic boarding school culture. This finding shows that leadership plays an important role in maintaining the sustainability of Islamic boarding school cultural values amidst the challenges of modernization.Contribution – This study contributes to the literature on educational leadership by proposing an adaptive authority model that combines religious legitimacy, cultural roots, and participatory managerial practices. Practically, this study provides insights for Islamic boarding school leaders and policymakers in designing leadership development programs, succession planning, and managerial innovation that balance cultural preservation with the demands of modern education.